Diastolic Function Assessment of Left and Right Ventricles by MRI in Systemic Sclerosis Patients. Issue 5 (8th March 2022) - Mousseaux, Elie; Agoston‐Coldea, Lucia; Marjanovic, Zora; Baudet, Mathilde; Reverdito, Guillaume; Bollache, Emilie; Kachenoura, Nadjia; Messas, Emmanuel; Soulat, Gilles; Farge, Dominique
Abstract : Background: Heart involvement is frequent although often clinically silent in systemic sclerosis (SSc) patients. Early identification of cardiac involvement can be improved by noninvasive methods such as MRI, in addition to transthoracic echocardiography (TTE). Purpose: To assess the ability of phase‐contrast (PC)‐MRI to detect subclinical left (LV) and right (RV) ventricular diastolic dysfunction in SSc patients. Study Type: Prospective. Population: Thirty‐five consecutive SSc patients (49 ± 14 years) and 35 sex‐ and age‐matched healthy controls (48.6 ± 13.5 years) who underwent TTE and MRI in the same week. Field Strength/Sequence: 5 T/PC‐MRI using a breath‐hold velocity‐encoded gradient echo sequence. Assessment: LV TTE ( E / E ′) and LV and RV PC‐MRI indices of diastolic function (LV early and late transmitral [ E M, EfM, A M, AfM ] and RV transtricuspid [ E T, EfT, A T, AfT ] peak filling flow velocities and flow rates, as well as LV [ E M ' ] and RV [ E T ' ] peak longitudinal myocardial velocities during diastole) were measured. Statistical Tests: Two‐tailed t ‐test, Wilcoxon test, or Fischer test for comparison of variables between SSc and healthy control groups; sensitivity, specificity, receiver‐operating‐characteristic (ROC) area under the curve (AUC) to assess discriminative ability of variables. A P ‐value <0.05 was considered statistically significant. Results: TTE LV E / E ′ and MRI E M / E M ' and E T / E T ' were significantly higher in SSc patients than in controls (8.27 ± 1.25 vs. 6.70 ± 1.66; 9.43 ± 2.7 vs. 6.51 ± 1.50; 6.51 [4.70–10.40] vs. 4.13 [3.22–5.75], respectively) and separated SSc patients and healthy controls with good sensitivity (68%, 71%, and 80%), specificity (85%, 94%, and 62%), and AUC (0.787, 0.807, and 0.765). LV EfM was significantly higher in SSc patients than in controls (347.1 ± 113.7 vs. 284.7 ± 94.6) as RVAfT (277 [231–355] vs. 220 [154–253] mL/sec) with impaired relaxation pattern (EfT /AfT, 0.95 [0.87–1.21] vs. 1.12 [0.93–1.47]). Data Conclusion: MRI was able to detect LV and RV diastolic dysfunction in SSc patients with good accuracy in the absence of LV systolic dysfunction at echocardiography. Use of MRI can allow to better assess the early impact of myocardial fibrosis related to SSc. Level of Evidence: 1 Technical Efficacy Stage: 2